PENGARUH KEPEMIMPINAN, MOTIVASI KERJA, DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA PT. PERUSAHAAN DAERAH AIR MINUM KOTA PADANG - Rahmatullah Pratama; Dike Rama Putra; Widia Firta (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to determine and analyze the influence of leadership, work motivation and communication on the performance of employees of PT. Padang City Water Supply Company. The population in this study were all employees of PT. Padang City Water Supply Company which amounted 287 employess. The sampling technique in this study used Proportional Random Sampling with a total sample of 75 employees at PT. Padang City Water Supply Company. The data analysis technique used is multiple linear regression analysis using SPSS version 23.0. The results showed that Leadership, Work Motivation and Communication had a positive and significant effect on Employee Performance at PT. Padang City Water Supply Company.